Results of a postoperative telemedicine trial after cardiac surgery and incorporation into practiceCentral MessagePerspective - Maren Downing, MEng; Christina Bull, NP; Teena Chavis, NP; Michael Modrow, PA-C; Gina McConnell, RN; Charles Harr, MD, MBA; Judson Williams, MD, MHS (JTCVS Open, 2023)
Objective: The study objective was to describe the implementation and results of a postoperative telemedicine program for adult cardiac surgery, including a clinical study and an organic postoperative telemedicine program aimed at reducing readmission rates and barriers to care. Methods: Patients undergoing coronary artery bypass grafting consented to enrollment in our Perfect Care study funded by The Duke Endowment including advanced practice provider–led postdischarge telemedicine services with data collection. There were 2 telemedicine visits at days 3 and 10 postdischarge using a live face-to-face video platform. Patients were provided with home wearables for heart rate monitoring, blood pressure cuffs, and scales. The success of the Perfect Care study led to the formation of our organic program, the Tele Heart Care, which was adapted to include a larger patient population while remaining structurally similar. Results: Fifty patients were enrolled prospectively between January and October 2021 in Perfect Care. The 30-day readmission rates for those enrolled was 4% compared with a 16% readmission rate for nonenrolled patients during this period. Furthermore, 36% of enrolled patients received medication modifications to optimize blood pressure, heart rate and rhythm, and fluid-volume status, or to treat infectious symptoms. Tele Heart Care enrolled 203 patients and was associated with a decrease in 30-day readmission rates in all cardiac surgery patients at our institution from 24% to 4% over a 6-month period. Conclusions: An advanced practice provider–led postdischarge telemedicine program after cardiac surgery can reduce hospital readmission and barriers to care, and improve patient satisfaction. With involvement of multiple stakeholders, a successful program can be launched despite the present state of national health system finances with limited human capital and constrained access to monitoring equipment.